Gross and delta efficiencies during uphill running and cycling among elite triathletes - Carlsson, M.; Wahrenberg, V.; Carlsson, M. S.; Andersson, R.; Carlsson, T. (European Journal of Applied Physiology, 2020)
Purpose: To investigate the gross efficiency (GE) and delta efficiency (DE) during cycling and running in elite triathletes. Methods: Five male and five female elite triathletes completed two incremental treadmill tests with an inclination of 2.5° to determine their GE and DE during cycling and running. The speed increments between the 5-min stages were 2.4 and 0.6 km h-1 during the cycling and running tests, respectively. For each test, GE was calculated as the ratio between the mechanical work rate (MWR) and the metabolic rate (MR) at an intensity corresponding to a net increase in blood-lactate concentration of 1 mmol/l. DE was calculated by dividing the delta increase in MWR by the delta increase in MR for each test. Pearson correlations and paired-sample t tests were used to investigate the relationships and differences, respectively. Results: There was a correlation between GEcycle and GErun (r = 0.66; P = 0.038; R2 = 0.44), but the correlation between DEcycle and DErun was not statistically significant (r = - 0.045; P = 0.90; R2 = 0.0020). There were differences between GEcycle and GErun (t = 80.8; P < 0.001) as well as between DEcycle and DErun (t = 27.8; P < 0.001). Conclusions: Elite triathletes with high GE during running also have high GE during cycling, when exercising at a treadmill inclination of 2.5°. For a moderate uphill incline, elite triathletes are more energy efficient during cycling than during running, independent of work rate.